RANCANG BANGUN ALAT PENGHITUNG BIBIT IKAN MENGGUNAKAN TOMBOL ANGKA (KEYPAD) SEBAGAI DATA INPUT - ., Riyan (Faculty of Engineering, Universitas Tanjungpura, 2016)
The process of counting fish seed is still done manually by scooped the baby Â fish using a simple steam shovel (similar scoop). The manual counting requires a lot of power and frequently encountered Â problems Â or Â obstacles Â such Â as Â timeÂ in Â counting Â and Â theÂ inaccuracyÂ of Â the calculation result. To resolve this problem required a fast and precise calculation method. Thus, the method of calculating fingerlings were designed using the keys number (keypad). The counting of baby fish, compare the input the keys number (keypad) and photodiode sensors. Output will be displayed to the seven segment viewer. If the seven segment show the same number, then the DC motor will work to close the tap line and the sensor stops working. Based on test results, the number of fish that measured 30, 50 and 100 individu. Test result